2023
DOI: 10.1002/chem.202203481
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Charge, Energy, and Hydrogen Transfer between the Backbone and Nucleobases in Isolated DNA Oligonucleotides

Abstract: Understanding how charge and energy, as well as protons and hydrogen atoms, are transferred in molecular systems as a result of an electronic excitation is fundamental for understanding the interaction between ionizing radiation and biological matter on the molecular level. To localize the excitation at the atomic scale, it was chosen to target phosphorus atoms in the backbone of gas-phase oligonucleotide anions and cations, by means of resonant photoabsorption at the L-and K-edges. The ionic photoproducts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…These results are in line with transfer of H from the initial site of single ionization, and the mechanisms proposed by the authors are shown in Scheme 3. We have obtained consistent results for the same molecular ion upon photoabsorption around the P L‐edge: since P atoms are located only in the backbone, it confirms that H transfer to nucleobases is triggered by photoabsorption at the backbone [133] . In the same article, we have provided experimental mass spectra of negative as well as positive ionic products of a deprotonated oligonucleotide after X‐ray photoabsorption around the P K‐edge energy, showing that specific absorption indeed occurs, and that abundant nucleobase cations (protonated and radical) are produced.…”
Section: Nucleic Acidssupporting
confidence: 68%
See 1 more Smart Citation
“…These results are in line with transfer of H from the initial site of single ionization, and the mechanisms proposed by the authors are shown in Scheme 3. We have obtained consistent results for the same molecular ion upon photoabsorption around the P L‐edge: since P atoms are located only in the backbone, it confirms that H transfer to nucleobases is triggered by photoabsorption at the backbone [133] . In the same article, we have provided experimental mass spectra of negative as well as positive ionic products of a deprotonated oligonucleotide after X‐ray photoabsorption around the P K‐edge energy, showing that specific absorption indeed occurs, and that abundant nucleobase cations (protonated and radical) are produced.…”
Section: Nucleic Acidssupporting
confidence: 68%
“…We have obtained consistent results for the same molecular ion upon photoabsorption around the P Ledge: since P atoms are located only in the backbone, it confirms that H transfer to nucleobases is triggered by photoabsorption at the backbone. [133] In the same article, we have provided experimental mass spectra of negative as well as positive ionic products of a deprotonated oligonucleotide after X-ray photo- [48] absorption around the P K-edge energy, showing that specific absorption indeed occurs, and that abundant nucleobase cations (protonated and radical) are produced. Since the oligonucleotide is initially deprotonated at the backbone, the positive charge on the nucleobase fragments means that charge and/or energy has been transferred from the backbone to the nucleobases.…”
Section: Oligonucleotidesmentioning
confidence: 95%
“…After exposure to the beam, the product ions are extracted into a high‐resolution reflectron time‐of‐flight mass spectrometer. Over the last years, we have used this technique to study VUV, soft X‐ray and ion induced dynamics in both protonated and deprotonated oligonucleotides [13,16,25–28] …”
Section: Electrospray Ionization and Radiofrequency Manipulation Of O...mentioning
confidence: 99%
“…Here, protonation of a nucleobase N‐site transforms an imine‐group into an amine‐group and the resulting N 1s shift leads to a shifted X‐ray absorption resonance that can be selectively adressed. Site‐selective photoionization of complex gas‐phase biomolecules currently is a rapidly growing field [14–17] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation